Peran Ekstrakurikuler Drum Band dalam Mengembangkan Kreativitas dan Disiplin Siswa di SDN Banyuajuh 3 Kamal - Agasi, Agil; Ananda, Natasya Ayu Datis; Rania, Nabila Putri; Nurtamam, Mohammad Edy; Fatonah, Siti (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to describe the role of drum band extracurricular activities in developing students’ creativity and discipline at SDN Banyuajuh 3 Kamal. This research uses a qualitative descriptive method with research subjects consisting of drum band students, the supervising teacher, and the drum band coach. Data collection techniques include observation, in-depth interviews, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results of the study show that drum band activities make a significant contribution to the development of students’ creativity. Creativity grows through practice in arranging music, organizing marching formations, and developing new ideas for performances. In addition, these activities also play an important role in shaping student discipline. Discipline is instilled through routines of arriving on time, adhering to practice schedules and rules, and taking responsibility for the musical instruments used. Collaborative training also encourages the development of other character traits such as cooperation, responsibility, and self-confidence. Overall, drum band extracurricular activities not only serve as a medium for expressing interest in music but also as an effective means of character building, especially in fostering creativity and discipline among elementary school students.